Phosphoinositides control the localization of HOPS subunit VPS41, which together with VPS33 mediates vacuole fusion in plants - Brillada, Carla; Krüger, Falco; Askani, Jana Christin; Schumacher, Karin (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The vacuole is an essential organelle in plant cells, and its dynamic nature is important for plant growth and development. Homotypic membrane fusion is required for vacuole biogenesis, pollen germination, stomata opening, and gravity perception. Known components of the vacuole fusion machinery in eukaryotes include SNARE proteins, Rab GTPases, phosphoinositides, and the homotypic fusion and vacuolar protein sorting (HOPS) tethering complex. HOPS function is not well characterized in plants, but roles in embryogenesis and pollen tube elongation have been reported. Here, we show that Arabidopsis HOPS subunits VPS33 and VPS41 accumulate in late endosomes and that VPS41, but not VPS33, accumulates in the tonoplast via a wortmannin-sensitive process. VPS41 and VPS33 proteins bind to liposomes, but this binding is inhibited by phosphatidylinosiltol-3-phosphate [PtdIns(3)P] and PtdIns(3,5)P2, which implicates a nonconserved mechanism for HOPS recruitment in plants. Inducible knockdown of VPS41 resulted in dramatic vacuole fragmentation phenotypes and demonstrated a critical role for HOPS in vacuole fusion. Furthermore, we provide evidence for genetic interactions between VPS41 and VTI11 SNARE that regulate vacuole fusion, and the requirement of a functional SNARE complex for normal VPS41 and VPS33 localization. Finally, we provide evidence to support VPS33 and SYP22 at the initial stage for HOPS–SNARE interactions, which is similar to other eukaryotes. These results highlight both conserved and specific mechanisms for HOPS recruitment and function during vacuole fusion in plants.